Groundwater recharge estimation for sustainable domestic water use a case study for the Talabaan Riverbasin in Misamis Oriental - Bagares, Rengie P.
Talabaan is a small rural watershed located twenty kilometers southwest of Cagayan de Oro City. It is a major source of water for the municipality of Naawan especially for groundwater use. Three pumping wells supply the current Level III municipal water system. These wells were designed to meet a ten-year projected water demand. The newest well was designed in 2016 because in 2014, the actual demand exceeded the projected demand back in 2003. For a long-term solution, a groundwater modelling study would have been a good option for the municipality but due to the lack of necessary data to conduct such, this study focused on estimating the average annual recharge for the entire catchment. Using the soil moisture accounting algorithm of HEC-HMS, a watershed model was successfully calibrated and validated by comparing the simulated outflow with the observed streamflow generated through drainage-area ratio method. The error indices and their corresponding values used in the model calibration are the following: Mean Signed Difference (-0.009cms), Root Mean Squared Error (1.92cms) and Mean Absolute Error (0.79cms), Nash-Sutcliffe Efficiency (0.487), Percent Bias (-0.65%) and Percent Error in Volume (-0.32%). By simulating the runoff from 2001 to 2012, the average annual recharge for the entire catchment was computed to be 97mm or 5.4% of the average annual precipitation. The safe yield is 5.815MCM/yr. This value is 9.5MCM lower than what is recommended by NWRC. If this yield is solely used by Naawan, its annual consumption exceeds the safe yield in 2119. From that year onwards, any addition to the annual demand is not allowed. In terms of population, this can serve up to 114,036 people. This value shows that with proper design of the water distribution system, expansion of the service area to other neighboring town is feasible. Groundwater modelling is recommended to account the temporal and spatial variability of groundwater in developing pumping wells in the study area.